Implementation of Muslim-friendly hotel (MFH) in Malaysia. - Sarip, Amirah Nabilah; Md. Baharudin, Md Hamzaimi Azrol; Abdul Rasol, Lokman; Che Hassan, Nurul Hidayah; Mohd Zahari, Siti Zafrina; Othman, Muhammad Muzakkir (Journal of Islamic, Social, Economics and Development, 2025)
Malaysia's tourism industry has witnessed significant growth in Muslim-friendly hospitality services, yet less than 10% of hotels achieve formal accreditation despite the country's consistent ranking as the world's top Muslim travel destination. This qualitative study explores the concept, characteristics, and implementation barriers of Muslim-Friendly Hotel (MFH) services in Malaysia through in-depth interviews with five industry experts. The research reveals that MFH services encompass halal food provision, prayer facilities, gender-segregated recreational areas, and staff conduct aligned with Islamic principles. Key findings identify three primary barriers: regulatory ambiguity, lengthy halal certification processes, and insufficient infrastructure development. The study distinguishes between Muslim-friendly and Shariah-compliant hotels, highlighting varying levels of Islamic compliance standards from MS 2610:2015 to comprehensive Shariah governance. Despite Malaysia's leadership in halal tourism, operational challenges including financial concerns about alcohol restrictions and costly facility modifications hinder widespread adoption. The research provides practical insights for hotel operators and policymakers to enhance Malaysia's competitive position in the growing global Muslim tourism market, projected to reach US$300 billion by 2026.